The assassin bug Pristhesancus plagipennis produces two distinct venoms in separate gland lumens - Andrew A. Walker (Nature Portfolio, 2018)
Venom can be used both offensively for prey capture and defensively to deter predators. Here, Walker and colleagues demonstrate that the assassin bug Pristhesancus plagipennis has two distinct venom glands that produce venoms with distinct compositions that can be elicited by different stimuli.